Educación infantil en Perú y América Latina: un desafío ante las múltiples infancias - Didonet, Vital (2012)
This text invites the reader to reconsider concepts that adults—parents and teachers— have about children. Moreover, to rethink the concepts on policies for childhood and practices of care and education, which are based on generic and universal concepts or that have been imposed by hegemonic cultures.What is defined as child’s right and family, society and State duty result from the knowledge gathered by the sciences that have investigated the human development in the first years of life, among them, more recently, sociology and anthropology of the childhood, as well as from our experience in the personal andconcrete care for the children. Therefore, the look that captures the universal and generic, and the one that meets the individual and historical in the children and in childhood complement each other to help us become better educators and their closer companions in the adventure of life. Different perspectives, from distinct points of view, enhance our vision on the children, allowing us a more faithful representation of who truly are these little human beings, so alike and distinct among them